Industrial and Storm Water Treatment and Recirculation Reuse in Feni Industry - Kavadarci - Petko Pelivanoski; Zivko Veljanoski; Goce Taseski; Aleksandar Maletik (My University, 2010)
The appearance of longer droughts; intensive population growth in the arid areas; as well as continued scarcity of quality water are problems, which occur more frequently lately. Therefore, the idea of finding a new reliable alternative water source is considered. Reuse of industrial wastewater is an important strategy for reducing freshwater consumption and wastewater generation. From an economic perspective, industrial wastewater reuse reduces the costs of fresh water supply and wastewater disposal. Many industrial users of fresh water are under increasing pressure to reuse water within their facilities. Their goal is to minimize the amount of fresh water use and waste water that is discharged to a receiving stream. The paper presents a method of industrial and storm waste water treatment from the ferro-nickel production of “Feni Industries” - Kavadarci and its recirculation water reuse in the technological process either. This way the both dual economic and environmental benefits are achieved. First, with the industrial waste water treatment and its recirculation reuse significantly is reduced the use of fresh water. Second, more fresh water remains to the agriculture. And the last but not the least, by reducing the amount of waste water that is being discharged into recipient, an environmental benefit is achieved.
Keywords: Industrial waste water treatment; storm water; recirculation